1991
DOI: 10.33584/jnzg.1991.53.2008
|View full text |Cite
|
Sign up to set email alerts
|

Early summer pasture control: what suits the plant?

Abstract: Plugs of sheep-grazed, ryegrass-dominant pasture were transplanted to a glasshouse, in order to make detailed studies of tiller appearance from the base of flowering tillers in late spring-early summer. In 2 experiments, cutting treatments which reduced the opportunity for transport of assimilate from parent flowering tillers to daughter tillers markedly reduced both numbers of daughter tillers formed and their size. In one of the studies, proportion of radioactive carbon dioxide fed to flowering tille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
4

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 11 publications
1
20
1
4
Order By: Relevance
“…A study conducted at the single tiller level by Matthew et al . () showed that the most favourable option is to delay the moment of elimination of reproductive stems until anthesis, a management referred to as ‘late control’. These results were also confirmed at the paddock scale (Da Silva et al ., ; Hernández‐Garay et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted at the single tiller level by Matthew et al . () showed that the most favourable option is to delay the moment of elimination of reproductive stems until anthesis, a management referred to as ‘late control’. These results were also confirmed at the paddock scale (Da Silva et al ., ; Hernández‐Garay et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Tanto o número como o tamanho dos perfilhos aumentam quando se eleva a translocação de carboidratos de reserva, contudo, isto somente ocorrerá se os produtos da fotossíntese e/ou metabolismo, bem como os carboidratos não estruturais estocados, sofrerem uma redistribuição dos perfilhos pais para os filhos . Nos casos onde os perfilhos pais são removidos inteiramente ou a translocação destes para os filhos é reduzida devido à competição com o desenvolvimento da inflorescência, o número e o tamanho dos novos perfilhos são reduzidos (Matthew & Chu, 1991).…”
Section: A Dominância Apical Controle Hormonal E Translocação De Resunclassified
“…Esses efeitos podem levar ao acúmulo de material morto e de caule no relvado, resultando em alta massa de forragem e, desta forma, a produção animal pode ser restringida pela baixa qualidade da forragem acumulada (Korte et al, 1984). testou uma estratégia alternativa de manejo proposta e avaliada por Korte (1982); Korte et al (1984); Matthew & Chu (1991) e Matthew (1992), porém utilizando e avaliando o desempenho produtivo de vacas leiteiras. Esse manejo alternativo chamado "controle tardio de pastejo" utilizado na primavera, difere da forma tradicional de utilização das pastagens na Nova Zelândia durante esse período e consiste no "atraso" para realização de pastejo intenso até que as plantas atinjam o estádio fenológico da antese.…”
Section: Manejo Do Perfilhamento E Produtividade Da Pastagemunclassified
See 2 more Smart Citations